Oreocharis sanglocii (Gesneriaceae), a new species from Hoang Lien Son Range, north-western Vietnam - Nguyen, Khang Sinh; Averyanov, Leonid V.; Nguyen, van Canh; Nuraliev, Maxim S.; Lyskov, Dmitry F.; Wen, Fang; Wu, Lei; Lin, Che Wei (Phytotaxa, 2025)
Oreocharis sanglocii, a new species discovered in Hoang Lien Son Range of north-western Vietnam, is described and illustrated. The new species is characterized by leaf blade much longer than petiole and distinctly longer than wide, many-flowered inflorescence, light yellow to almost white corolla with purple-maroon markings at throat, narrow corolla tube constricted at throat, stamens with distally pubescent filaments and free (and not coherent) anthers, glabrous pistil and capsule, and peltate stigma. Oreocharis sanglocii is most close to O. blepharophylla, being readily distinguishable from it by more numerous secondary veins of leaf blade, inflorescence with up to 20 flowers, yellowish outer surface of corolla tube, hairy stamen filaments, and free anthers. The new species is also similar to the yellow-flowered O. tsaii and O. zhenpingensis. Available information on the species phenology, ecology and conservation status is presented, along with the taxonomic notes. This discovery is in line with the idea that within the territory of Vietnam Oreocharis is most diverse in the northern areas. It brings the number of species of the genus documented from Vietnam to twelve.